A Maximum Principle for Elliptic and Parabolic Equations with Oblique Derivative Boundary Problems (Journal of Partial Differential Equations, 2020)
This paper prove a maximum principle for viscooity solutions of fully nonlinear, second order, uniformly elliptic and parabolic equations with oblique boundary value conditions.
Keywords: Maximum principle; viacosity solution; fully nonlincar equations